Update on Seminal Vesiculitis in Stallions - Scheeren, Verônica F.C. [UNESP]; Sancler-Silva, Yame F.R.; El-Sheikh Ali, Hossam; Kastelic, John P.; Alvarenga, Marco A. [UNESP]; Papa, Frederico O. [UNESP] (Elsevier, 2020)
Seminal vesiculitis in stallions reduces fertility and is often underdiagnosed. The most common cause is infection of seminal vesicles by bacteria capable of forming biofilms and a propensity for tissue persistence, for example, Pseudomonas aeruginosa. Achieving a clinical cure is challenging because of a high rate of recurrence. Systemic antibiotic therapy does not reach adequate therapeutic concentrations within the seminal vesicles; one alternative is endoscopy-guided, local antibiotic infusion into the gland lumen, with or without concurrent systemic antibiotics. Current diagnostic and therapeutic strategies for seminal vesiculitis are less than fully satisfactory, and several studies have been conducted to improve them. This review covers traditional and newer concepts regarding seminal vesiculitis, including diagnostic and treatment methods, management of stallions with this disorder, and authors’ experience with clinical cases.
Keywords: Accessory sex gland; Horse; Infection; Semen; Seminal vesicle